English language needs of non-native foreign students - Pawanchik, Shahrier; Kamil, Anton Abdulbasah; Hilmi, Mohd Faiz; Baten, Md Azizul (David Publishing, 2011)
This paper will investigate the English language needs of non-native foreign students who are studying at the University of Otago, New Zealand. These students comprise of students from Asia (China, Thailand, Korea, Qatar, Saudi Arabia, to name a few) and Europe.For these students, English is their second or third language and they face proficiency problems.To them, mastery of English is most important because all the courses in the university are taught in English and unless the students are proficient to operate in English, they will lose out and face difficulties in securing good grades for their subjects.Findings of this research will provide insights for the curriculum developers and English teachers at public universities especially in Malaysia that have been accepting students from Asia and the Middle East.The present curriculum need to be reviewed or a new curriculum need to be designed to meet the English needs of their non-native foreign students.